Pengaruh Islamicity Performance Index (IPI) terhadap Kinerja Keuangan Bank Umum Syariah Tahun 2018-2022 - Intan Nazmi Nurfajri; Sri Fadilah (Bandung Conference Series: Accountancy, 2024)
Abstract. This research is based on the phenomenon that occurred in Sharia Commercial Bank companies registered with the Financial Services Authority, which experienced a fairly large decline in financial performance. This research aims to determine the effect of the Islamicity Performance Index (IPI) which is proxied by the Zakat Performance Ratio (ZPR) on financial performance. This research was conducted on Sharia Commercial Bank companies registered with the Financial Services Authority (OJK) in 2018-2022. With the purposive sampling technique, a sample size of 8 banks was obtained. The research method used is a verification method with a quantitative approach. The data source used is secondary data obtained from the official website of each Sharia Commercial Bank. Hypothesis testing in this research uses multiple linear regression analysis. The proposed hypothesis was tested using Eviews 12. The research results showed that the Islamicity Performance Index (IPI), which was proxied by the Zakat Performance Ratio (ZPR), had an effect on financial performance. Abstrak. Penelitian ini didasarkan pada fenomena yang terjadi pada perusahaan Bank Umum Syariah yang terdaftar di Otoritas Jasa Keuangan, dimana mengalami penurunan kinerja keuangan yang cukup besar. Penelitian ini bertujuan untuk mengetahui pengaruh Islamicity Performance Index (IPI) yang diproksikan Zakat Performance Ratio (ZPR) terhadap kinerja keuangan. Penelitian ini dilakukan pada perusahaan Bank Umum Syariah yang terdaftar di Otoritas Jasa Keuangan (OJK) tahun 2018-2022. Dengan teknik pengambilan sampel Purposive sampling diperoleh sampel jumlah sampel 8 Bank. Metode penelitian yang digunakan adalah metode verifikatif dengan pendekatan kuantitatif. Sumber data yang digunakan adalah data sekunder yang diperoleh dari situs resmi masing-masing Bank Umum Syariah. Pengujian hipotesis dalam penelitian ini menggunakan analisis linier regresi berganda. Hipotesis yang diajukan, diuji menggunakan Eviews 12. Hasil penelitian menunjukkan bahwa Islamicity Performance Index (IPI) yang diproksikan Zakat Performance Ratio (ZPR) berpengaruh terhadap kinerja keuangan.